Exploring the skin whitening properties of natural products: A comprehensive review - Ha, Ly Hong Huong; Thu, Do Thi Anh; Thuy, Ho Thi Thach; Yen, Nguyen Thi Hong (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
Natural products have been gaining popularity in recent years as a safe skin-safe alternative solution to synthetic products on the market. In particular, natural ingredients have been found to have skin-whitening properties by inhibiting melanin production and reducing hyperpigmentation. This review provides the analysis of some mechanisms and effectiveness of natural products in achieving even skin tone and reducing the appearance of dark spots. Several natural ingredients, such as chemical compounds in licorice root, green tea extract, and vitamin C, have been tested for their ability to reduce tyrosinase activity and melanin synthesis, as well as for their anti-inflammatory and antioxidant properties. In addition, the selection of uses and further research into the safety and effectiveness of natural products. Overall, natural products represent a safe and effective solution to achieving brighter, more radiant skin.